LITERAL EQUIVALENCE IN MEANING-BASED TRANSLATION - A. Djawad Mubasyir (Deiksis, 2015)
This paper reports on a study that investigated the literal equivalence in meaning-based translation through a library exploration. The result of the study shows that as far as meaning is concerned, the context of situation is hypothesised to play an important role not only in finding the intended meaning in the source language (SL) text, but also in conveying the meaning equivalence through the lexico-grammatical system in the target language (TL) text. Based on this assumption, some evidence has been proposed to support that literal translation is problematic in meaning-based translation. If it has been found that there are problems with literal translation at word level and above word level up to the sentence level, it seems quite true that problems are even more prevalent at discourse levels and above.Keywords: Translation, Grammatical Equivalence, Textual Equivalence